Three New Species of Clonostachys (Hypocreales, Ascomycota) from China - Zhao-Qing Zeng; Wen-Ying Zhuang (Journal of Fungi, 2022)
Three new species of Clonostachys are introduced based on specimens collected from China. Clonostachys chongqingensis sp. nov. is distinguished by pale yellow to pale orange-yellow perithecia with a very low papilla, clavate to subcylindrical asci possessing ellipsoidal to elongate-ellipsoidal spinulose ascospores 13–16 × 4.5–5.5 μm; it has acremonium- to verticillium-like conidiophores and ellipsoidal to rod-shaped conidia. Clonostachys leptoderma sp. nov. has pinkish-white subglobose to globose perithecia on a well-developed stroma and with a thin perithecial wall, clavate to subcylindrical asci with ellipsoidal to elongate-ellipsoidal spinulose ascospores 7.5–11 × 2.5–3.5 μm; it produces verticillium-like conidiophores and ellipsoidal to subellipsoidal conidia. Clonostachys oligospora sp. nov. features solitary to gregarious perithecia with a papilla, clavate asci containing 6–8 smooth-walled ascospores 9–17 × 3–5.5 μm; it forms verticillium-like conidiophores and sparse, subfusiform conidia. The morphological characteristics and phylogenetic analyses of combined nuclear ribosomal DNA ITS1-5.8S-ITS2 and beta-tubulin sequences support their placement in Clonostachys and their classification as new to science. Distinctions between the novel taxa and their close relatives are compared herein.